Juan Pedro Musete, mercader de libros, en Medina del Campo - Torres Pérez, José María (Revista General de Información y Documentación, 2007)
In the XVI century, Medina del Campo has an important book commerce, first focused on the fairs and, after 1540, developed through the booksellers permanently settled down in that town. Kept in the Archive of the Royal Chancery from Valladolid, there is a lawsuit started out in 1541 and launched by Juan Brocar, printer and bookseller from Alcalá de Henares, against Pedro Sandón and Ginés Formil, merchants in charge of getting the amounts of money some booksellers must satisfy to Juan Pedro Musete, bookseller from Medina del Campo. This document allows us to know thirty seven people’s names, Musete’s customers and booksellers scattered all over Spain. Moreover, it affords us the opportunity to discover some books spread throughout some university and cathedral cities.